Phospholipids enhance the binding of peptides to class II major histocompatibility molecules. - Roof, R W (1990)
The binding of a lysozyme and ovalbumin peptide to purified class II major histocompatibility molecules in detergents was increased by the addition of certain lipids. Natural lipids from B lymphoma cells enhanced the binding and so did phosphatidylcholine, phosphatidylserine, phosphatidylinositol, and cardiolipin. Phosphatidylethanolamine, sphingomyelin, and cholesterol had no effect. There was no major difference between the effects of a phospholipid and its lyso derivative. As studied with phosphatidylcholine, the increase in peptide binding was also dependent on the fatty acid composition of the lipid. The binding affinity was increased 10- to 50-fold in the presence of lipid as a result of an increase in the association rate while the off-rate remained essentially unchanged. Our results suggest that lipids, directly or indirectly, induce conformational changes in class II molecules that favor their peptide-binding property.